Photocatalytic Degradation of Dye Pollutant Acid Yellow-17 by La Doped TiO2/Indium-Tin Oxide Thin Layer Photocatalytic Electrode - Wang, Wei-Fu; Hu, Cheng-Ling; Hsieh, Yung-Hsu (Asian Journal of Chemistry, 2013)
La-doped TiO2 photocatalytic electrode has been successfully synthesized using tetraisopropyl orthotitanate, isopropyl alcohol, acetic acid and La2O3 as precursors by sol-gel method. Different molar raitos of La/Ti were supported on indium-tin oxide glass to product photocatalytic electrodes. All catalysts have been further characterized by using XRD, XPS and contact angle analysis. The La/Ti molar ratio 0.05 photocatalytic electrode shows the best decolorzation and mineralization rate after 4 h reaction. Applied potential would effectively increase the decolorization rate under visible light irradiation.